Engineering austenite/martensite mesostructured materials by controlled localised laser treatments in a Fe–Ni–C alloy. (March 2023) - Breukelman, H.J.; Hermans, M.J.M.; Santofimia, M.J.; Hidalgo, J.
Graphical abstract: Highlights: The mesostructure of α'/ γ steel was tailored by varying laser parameters. Gradient microstructures resulted from steep temperature and heating rate gradients. Formulated model predictions are in agreement with observed microstructures. Specimen thickness and absorptivity determine laser heat penetration. High heating rates produced pseudo-displacive α' → γ and recrystallization. Abstract: Localised laser treatments enable the creation of sophisticated austenite/martensite mesostructures in Fe–Ni–C steel with the potential of achieving enhanced mechanical performance. The control of phase topology is essential to modify the properties of these structures on demand and requires a profound understanding of the effect of the processing parameters on the development of the different phases upon the application of laser treatment. In this work, the microstructure evolution under exceptional gradients in temperature and heating rates is thoroughly investigated. The extent of the laser-affected zone and the heat input were tailored by varying laser parameters and specimen thickness, based on a model that considers transient material properties and the coupling between temperature and microstructure. The predicted temperature fields resulted in a complex interplay between martensite to austenite phase transformation and martensite tempering. Considering the high heating rates of up to 25000 K/s and the observed microstructures, it is suggested that austenite was formed by a pseudo-displacive mechanism and subsequently fully recrystallised in the zones most directly affected by the laser heat source. A smooth strength transition from austenite to martensite, affected by the laser parameters, could be exploited for more effective deformation mechanisms and improved material mechanical properties.